FORMATION OF A POSITIVE IMAGE OF UKRAINE IN THE WORLD - Kalinkina, Natalia; Anna (Pressing Problems of Public Administration, 2021)
The article investigates issues of the state image in the context of democratic changes in Ukraine. The author proves that the image of the state in international dimension is one of the main factors of international relations” development. The analysis of formation and realization of foreign image policy of Ukraine in the world is carried out. It has been proven that a positive perception of the state within the country and in the world is the key to the success of global political, social and economic movements, which are reforms.